Pelestarian dan Pengembangan Seni Ajeng Sinar Pusaka pada Penyambutan Pengantin Khas Karawang - Rosikin Wikandia (PANGGUNG, 2016)
ABSTRACT Ajeng art preservation Hamlet  origin  Bambu  Duri, Karangpawitan.  Karawang,  many obstacles.  Passive  role of the local artist community,  the lack of regeneration  culture  of origin, not pro-active  good relations  between relevant  agencies as well as the entry  of modern art, the art of Ajeng  undeveloped and eroded extinction.  Ajeng art is a kind of art that has its peculiari- ties such as art pangajeng-ngajeng  (Pangwilujeng)  accompanied by Soja dances that were held at the welcoming  ceremony  the bride or the guest  of honor.  Through  research  with qualitative descriptive approach to the socio-cultural  aspects in a systematic, empirical, and cultural  theory is expected to  be the  presentation  of Ajeng  art Maya art aesthetic  tradition  and loved young people in the conservation and development  of the  art of Ajeng. Keywords: Ajeng,  Dance Soja     ABSTRAK Pelestarian seni Ajeng asal Dusun Bambu Duri, Karang Pawitan. Kabupaten Karawang, banyak mengalami hambatan. Pasifnya peran komunitas seniman setempat, kurang adanya regenerasi budaya asal, tidak pro aktifnya hubungan baik antara dinas terkait serta masuknya kesenian modern, maka seni Ajeng tidak berkembang dan tergerus kepunahan. Seni Ajeng merupakan jenis seni yang memiliki kekhasan seperti seni pangajeng-ngajeng (Pangwilujeng) dengan diiringi tarian Soja yang biasanya dilaksanakan pada acara upacara pengantin atau penyambutan tamu kehormatan. Melalui penelitian dengan pendekatan deskriftif kualitatif pada aspek sosial budaya secara sistematis, empiris, dan teori budaya diharapkan seni Ajeng menjadi penyajian seni Ajeng yang estetik tradisi dan dicintai generasi muda dalam rangka pelestarian dan pengembangan seni Ajeng. Kata kunci: Ajeng, Tari Soja